An Environmental Flow Framework for Riverine Macroinvertebrates During Dry and Wet Seasons Through Non-linear Ecological Modeling - Luo, Qingyi; Chiu, Ming-Chih; Tan, Lu; Cai, Qinghua (Frontiers in Ecology and Evolution, 2021)
A suitable environmental flow is critical for the functional maintenance of riverine ecosystems. Hydropower plants alter the flow regime by decreasing or even drying up the streamflow downstream of the dams, thereby affecting ecosystem sustainability. In this study, we aimed to develop a robust environmental flow framework that can provide scientific evidence for sustainable water resource management. Using ecological niche modeling based on nonlinear responses of species to habitat factors, we assessed the environmental flow in the Xiangxi River Basin of Central China during dry and wet seasons from a multi-year perspective. The most abundant macroinvertebrate taxon (i.e., Baetis) was selected for model testing. The results showed seasonal differences in the minimum ecological water requirements and optimal environmental flow. These two hydrological metrics were higher during the wet season than during the dry season. During the dry season, the minimum ecological water requirement of Baetis was 1.3 m3∙s-1 and the optimal environmental flow was 1.6 m3∙s-1. During the wet season, the minimum ecological water requirement of Baetis was 2.5 m3∙s-1 and the optimal environmental flow was 2.6 m3∙s-1. Our study provides a theoretical basis for the robust management of water resources in river basins.